Internal Factor Analysis In Management Control System Design With Organizational Objectives As Intervening Variables In Blood Transfusion Unit PMI Jember - widagdo, suwignyo (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2019)
This study aims to analyze the structure of the organization, program structure, information structure, administrative factors, behavioral factors and cultural factors in the design of control system management with organizational goals as an intervening variable. Data is taken from questionnaires that have been filled out by several respondents. Determination of the sample is done using the Slovin formula. The overall sample consisted of 30 respondents who were employees of UTD PMI Jember Branch in 2018. The results showed that the organizational structure showed a significant influence on organizational goals. While the variable program structure, information structure, administrative factors, behavioral factors and cultural factors do not show a significant effect on organizational goals. Variable organizational structure, program structure, information structure, administrative factors, behavioral factors and cultural factors show no significant effect on partial. Management control system design but simultaneously influenced. Organizational goals can be intervening variables between program structure, information structure, behavioral factors and cultural factors in the design of management control systems.Whereas organizational goals cannot be intervening variables between organizational structure and administrative factors in the management control system design.